Correlation between geometric parameters of the left coronary artery and hemodynamic descriptors of atherosclerosis: FSI and statistical study. - Pinho, N.; Castro, C. F.; António, C. C.; Bettencourt, N.; Sousa, L. C.; Pinto, S. I. S. (Medical & Biological Engineering & Computing, 2019)
The hemodynamics conditioned by coronary geometry may play an important role in the creation of a pro-atherogenic environment in specific locations of the coronary tree. The aim of this study is to identify how several geometric parameters of the left coronary artery - cross-section areas, proximal left anterior descending artery length, angles between the branches and the septum, curvature and tortuosity - can be related with hemodynamic descriptors, using a computational fluid-structure interaction method. It is widely accepted that the hemodynamic indicators play an important role in identifying possible pro-atherogenic locations. A statistical study, using Pearson correlation coefficient and P value, was performed for a population study of 8 normal human left coronary arteries presenting right-dominant circulation. Within the study cases, arteries with high caliber (r = 0.88), high angles LMS-LAD (r = 0.49), LAD-LCx (r = 0.57) and LAD-Septum (r = 0.52), and high tortuosity LMS-LCx (r = 0.63) were correlated with a hemodynamic behavior propitious to plaque formation in the left anterior descending artery. In contrast, high proximal left anterior descending artery length (r = -0.41), high angle LMS-LCx (r = -0.59), high tortuosity LMS-LAD (r = -0.56) and LAD-LCx (r = -0.55) and high curvature of LMS (r = -0.60) and LCx (r = -0.56) can lead to non-favorable hemodynamic conditions for atheroma formation. Graphical abstract.